2020
DOI: 10.1101/2020.04.18.048264
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chronic Developmental Lead Exposure increases μ-Opiate Receptor Levels in the Adolescent Rat Brain

Abstract: Opioid use and abuse has reached epidemic proportion in the United States resulting in a significant numbers of deaths due to overdose. While environmental factors are implicated in opioid addiction, less is known about the role of exposure to environmental pollutants on the brain opioid system. Human and preclinical studies have suggested an association between childhood lead (Pb 2+ ) intoxication and proclivity to substance abuse and delinquent behavior. Opioid receptors are involved in the biological effect… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…Dopamine receptors can form heteromers with opioid receptors, D2 dopamine receptors, and NMDA receptors, among others (reviewed in Derouiche and Massotte, 2019), and they can be involved in substance use disorder. Our data shows that Pb 2+ exposure alters D1R levels in several brain regions implicated in substance abuse and previous studies from our group show that Pb 2+ exposure affects other neurotransmission systems, which could translate at the behavioral level (Guilarte and McGlothan, 2003;Neal et al, 2010Neal et al, , 2011Stansfield et al, 2015;Albores-Garcia et al, 2021). Additionally, other studies have shown the role of environmental toxin exposures on drug sensitivity.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…Dopamine receptors can form heteromers with opioid receptors, D2 dopamine receptors, and NMDA receptors, among others (reviewed in Derouiche and Massotte, 2019), and they can be involved in substance use disorder. Our data shows that Pb 2+ exposure alters D1R levels in several brain regions implicated in substance abuse and previous studies from our group show that Pb 2+ exposure affects other neurotransmission systems, which could translate at the behavioral level (Guilarte and McGlothan, 2003;Neal et al, 2010Neal et al, , 2011Stansfield et al, 2015;Albores-Garcia et al, 2021). Additionally, other studies have shown the role of environmental toxin exposures on drug sensitivity.…”
Section: Discussionsupporting
confidence: 73%
“…The Pb 2+ exposure paradigm used in this study did not change the body weight gain of Pb 2+ -exposed rats at PN28, PN50, or PN120 (Albores-Garcia et al, 2021). BLL were significantly higher in both exposed groups in male and female rats, at all evaluated ages (Albores-Garcia et al, 2021).…”
Section: Animal Weight and Blood Pb 2+ Levelsmentioning
confidence: 66%
See 3 more Smart Citations